Compatibility Study of Ketoprofen With Selected Excipients Used in Solid Dosage Forms: Experimental Design Approach - Joanna Ronowicz-Pilarczyk (Polskie Towarzystwo Farmaceutyczne, 2023)
A good understanding of the physico-chemical characteristics of a drug substance and excipients is necessary to obtain a safe and effective drug dosage form. Based on the current recommendations of the regulatory agencies (EMA, FDA) regarding the implementation of the Quality by Design concept at the drug product development stage, this article is focused on the application of the experimental design approach at the preformulation studies. The purpose of this work was the implementation of experimental design methodology in a compatibility study between ketoprofen (non-steroidal anti-inflammatory drug) and selected solid dosage forms excipients. The fractional factorial design was used to generate a matrix of multi-component mixtures of ketoprofen and selected excipients. In order to accelerate any chemical incompatibilities, the received mixtures were exposed to elevated temperature and humidity (60°C/75% RH) in a climate chamber for 3 weeks. The ketoprofen-excipients compatibility was studied by means of the RP-HPLC method. It was confirmed that the type of disintegrant had a strong impact on ketoprofen degradation. The incompatibility in mixtures of ketoprofen with sodium starch glycolate was indicated. According to literature data, it may be the result of a decrease in crystallinity and thus a decrease in the stability of ketoprofen in the presence of sodium starch glycolate. The effects of the other types of excipients were statistically insignificant (p > 0.05). The applied experimental design methodology allowed for a rational selection of optimal excipients and thus, this approach may support significantly decision-making in the pharmaceutical industry.